The ivory damsel is bored: changing female dynamics for the Ovidian Galatea in Michelangelo Antonioni’s "Identificazione di una Donna" (1982) - Sílvia Catarina Pereira Diogo (Cinema & Território)
The Pygmalion myth as told by Ovid gave rise to a literary tradition that cinema sought to eternalize in films such as Pygmalion et Galathée (Méliès, 1898), Funny Face (Donen, 1957), etc. In these, normally the female is submissive to the male. The same premise may also be indirectly found in Antonioni’s Identificazione di una Donna (1982), but under a different concoction. Instead of adopting a submissive stance towards Niccolò, Mavi, the ad hoc Galatea, is seen as a passive character in the way that she does behave uninterested towards loving Niccolò, the Pygmalion figure. This poise is characteristic of the typical ennui that permeates female characters in Antonioni’s films. This paper attempts to intersect the dramatis personae of the Ovidian myth with characters Niccolò and Mavi from Antonioni’s film and provide further analysis on the possibility of Mavi becoming a powerhouse for the liberation of the ivory damsel in contemporary narratives. Whilst conditioned to a specific environment of Antiquity, Ovid’s ivory jeune is set to behave according to what is expected of her — a voiceless extension of Pygmalion. Conversely, when exposed to contemporary metaliterary media, the ivory damsel can set free and rebel against a dominant male taxonomy.